Fatal Basilar Thrombosis Possibly Related to Minor Cervical Trauma: A Case Report - Elmaz Shaqiri; Gentian Vyshka; Admir Sinamati; Besim Ymaj; Zija Ismaili (Case Reports in Medicine)
Background. Basilar thrombosis is a potentially fatal event, whose traumatic etiology has been repeatedly stated. Methods. We performed the autopsy and the microscopic examination of the brain stem structures from an individual, whose sudden death raised logical suspicions regarding the causative factor. Results. The brain was swollen and clearly hyperemic; a massive basilar thrombus with complete occlusion of the median segment of the basilar artery was macroscopically seen. The brainstem showed an infarcted zone in the pons, with secondary hemorrhagic changes, mainly in the form of multiple petechial hemorrhages. Pontine arteries showed extensive alterations, mainly in the form of severed endothelium, which suggested a thrombotic-traumatic mechanism as the main etiological factor. Conclusions. Minor injuries, such as slight whiplashes, abrupt neck movements, neck trauma related to the slowing down of the vehicles, and critical neck positioning, can all of them explain a thrombotic event in the basilar artery, leading to a fatal occurrence. Other risk factors may obviously concur, but their importance seems unclear.